Positive association between weight-adjusted-waist index and hyperuricemia in patients with hypertension: The China H-type hypertension registry study - Zhao, Peixu; Shi, Weidong; Shi, Yumeng; Xiong, Yurong; Ding, Congcong; Song, Xiaoli; Qiu, Guosheng; Li, Junpei; Zhou, Wei; Yu, Chao; Wang, Tao; Zhu, Lingjuan; et al. (Frontiers in Endocrinology, 2022)
Background and aims The relationship between the new obesity index weight-adjusted-waist index (WWI) and hyperuricemia is unclear. We aimed to explore the association of the WWI and hyperuricemia among the hypertensive population. Methods A total of 14,078 hypertension participants with complete data were included in our study. WWI was calculated by waist circumference divided by the square root of weight. Specifically, men with 420 μmol/L and women with 360 μmol/L were considered to have hyperuricemia. Results The prevalence of hyperuricemia was 61.1% in men and 51.4% in women. On the whole, multivariate logistic regression analyses found that there was a linear positive correlation of WWI with hyperuricemia in both men (OR: 1.37; 95%CI: 1.25, 1.49) and women (OR: 1.35; 95%CI: 1.26, 1.45). Subgroup analysis found that the relationship between WWI and hyperuricemia was stable in stratified subgroups (all P-interactions >.05). Conclusion WWI showed a positive association with hyperuricemia among hypertension patients.